2020
DOI: 10.1364/ol.404760
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nonlinear and saturable absorption on laser lift-off threshold of an oxide/metal structure

Abstract: In this work, a new model of effective lift-off threshold of oxide/metal target is presented. The influence of nonlinear processes in the oxide layer on its removal from the metallic samples using picosecond laser was investigated. Nonlinear and saturable absorption in the layer was incorporated into modeling for prediction of effective laser lift-off threshold fluence change with varying peak intensities in z-scan type experiment for the first time. The new model coincides well with the experimental results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Incoming laser irradiation first interacts with the oxide, with a significantly higher ablation threshold 27 and only afterwards with the metal itself. Žemaitis et al 28 demonstrated that a copper sample covered in a Cu 2 O oxide has three oxide transmission cases described by different z/z R values, where Z R = π w 0 2 /(λ M 2 ) z R is the Rayleigh length, z is the sample position, λ is the wavelength of the laser irradiation, and M 2 is the quality parameter of the Gaussian beam. The three transmission cases are as follows: when the sample is very out of focus and z / z R ≫> ±1 linear absorption is dominant with a transmission value of T 0 ≈ 60%, when the sample is not far from focus and z / z R ≈ ±1 and is in the saturable absorption region with a transmission value of T 0 ≈ 99%, and when the sample is in focal position with z / z R ≈ 0, where nonlinear absorption exceeds absorption saturation in the oxide layer and transmission drops down to T 0 ≈ 44%.…”
Section: Resultsmentioning
confidence: 99%
“…Incoming laser irradiation first interacts with the oxide, with a significantly higher ablation threshold 27 and only afterwards with the metal itself. Žemaitis et al 28 demonstrated that a copper sample covered in a Cu 2 O oxide has three oxide transmission cases described by different z/z R values, where Z R = π w 0 2 /(λ M 2 ) z R is the Rayleigh length, z is the sample position, λ is the wavelength of the laser irradiation, and M 2 is the quality parameter of the Gaussian beam. The three transmission cases are as follows: when the sample is very out of focus and z / z R ≫> ±1 linear absorption is dominant with a transmission value of T 0 ≈ 60%, when the sample is not far from focus and z / z R ≈ ±1 and is in the saturable absorption region with a transmission value of T 0 ≈ 99%, and when the sample is in focal position with z / z R ≈ 0, where nonlinear absorption exceeds absorption saturation in the oxide layer and transmission drops down to T 0 ≈ 44%.…”
Section: Resultsmentioning
confidence: 99%